Dampak Marketing Syariah terhadap Minat Beli Konsumen Di Toko Lancar Elektronik Ponorogo (Perspektif Theory Of Planned Behavior) - Suprianto, Suprianto; Rois, Adib Khusnul; Syukroni, Azid; Candrakusuma, Muslih (Musyarakah: Journal of Sharia Economic (MJSE), 2023)
This research was carried out with the aim, firstly, to find out how the management and marketing of the Current Electronics Store in Ponorogo Regency is. Second, to find out about the application of sharia marketing in increasing consumer buying interest at the Lancar Electronics Shop, Ponorogo Regency. The object of this research is consumers of the Current Electronics Store, Ponorogo Regency. The data in this research are primary and secondary data. The data collection method used in this research is observation, interviews and documentation. The data analysis method used in this research is qualitative descriptive analysis. The results of this research, first. The operational standards applied are that employees must be Muslim/Muslim women, able to read the Koran and obey the 5 daily prayers. Judging from the payroll system, employee salaries are on time and if a customer files a complaint, the employee must serve him patiently in handling it. Second. Toko Lancar Electronics Ponorogo implements a sharia marketing strategy to increase consumer buying interest in accordance with the characteristics and practices of sharia marketing as taught by Rasulullah SAW. Which consists of four elements, namely theistic (rabbaniyyah), ethical (akhlaqiyyah), realistic (al-waqi'iyyah) and humanistic (insaniyyah).